Pengembangan Efikasi Diri Siswa SMK dalam Menentukan Keputusan Karir Melalui Layanan Bimbingan Kelompok - Rois Nafi'ul Umam (Institut Agama Islam Negeri (IAIN) Curup, 2021)
A career as a process that individuals will undertake in the future, needs to be carefully prepared since they are at the SMA / SMK education level. Through careful career planning, students can easily make the right decisions about their careers. As for the obstacles that occur, students cannot make their own career decisions which are caused by low self-efficacy/self-confidence. The purpose of this study is to explain the role of counseling guidance services in developing student self-efficacy in achieving career decisions. This type of research is field research with a qualitative approach and a descriptive-analytical method. Data collection techniques were carried out by observation and interviews. Symptoms of low self-efficacy experienced by students are 1) difficulty to make career decisions, 2) not confident in their career plans, 3) worry that they are not absorbed in the world of work. Group guidance services are carried out in 4 stages, namely the initial stage, the transition stage, the activity stage, and the final stage. The results of the counseling service show that students have good self-efficacy, can make career decisions, are confident, and do not experience worries about their career plans.